Two Ways of Processing Language: Associative Memory and Computational Rules in the Case of Modern Polish - Koziarski, Mirosław; Krysiak, Adrian P. (Investigationes Linguisticae, 2011)
This paper discusses associational and computational approaches to language and cognition with a special focus on modern Polish. The authors indicate the sources for both views and try to combine these views in order to answer the underlying question of how language is processed. The analysis of Polish morphology (scil. verb inflection) has shown that such a combination is possible and scientifically valuable but still more specific research on the neuronal correlates of linguistic behaviours is needed.